2012
DOI: 10.5897/ajbm11.2860
|View full text |Cite
|
Sign up to set email alerts
|

Review of relationship between dividend policy and performance: Evidence of Irans capital market

Abstract: The aim of this study is to review the relationship between dividend and company performance on equity capital markets in Iran, consequently two groups of performance indexes based on economical trend and accounting trend were studied. In this study, library method of collecting information was employed and the numbers of 93 companies whose required information were available were chosen in 6-year-old study (2004 to 2009). This study is correlation based on method and nature and it has been used for correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…They suggested that underinvestment happens because the management cautiously chooses only secured investments and distributes the excess cash to shareholders as dividends. While trying to advance the issue of dividend policy and firm performance, Zanjidar & Seifi (2012) investigated the relationship between dividend and company performance. Conse-quently, two groups of performance indices based on economic trend and accounting trend were studied.…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…They suggested that underinvestment happens because the management cautiously chooses only secured investments and distributes the excess cash to shareholders as dividends. While trying to advance the issue of dividend policy and firm performance, Zanjidar & Seifi (2012) investigated the relationship between dividend and company performance. Conse-quently, two groups of performance indices based on economic trend and accounting trend were studied.…”
Section: Empirical Frameworkmentioning
confidence: 99%